Construction and maintenance of a fuzzy temporal ontology from news stories. (1st January 2011) - Drury, Brett; Almeida, J.J.; Morais, M.H.M.
Construction of business ontologies from news sources can produce a detailed representation of the chosen area, but the Ontology may over time gather errors because information can become rapidly outdated. The two stage strategy described in this paper attempts to identify outdated relations in an Ontology by affixing a confidence score to each relation and decaying the relation until a preset value where it is deleted or archived. The relation score is refreshed if the information is repeated in a news story. An evaluation demonstrates that over time erroneous information is removed and new information is added to the Ontology.